1991
DOI: 10.3109/03093649109164653
|View full text |Cite
|
Sign up to set email alerts
|

The care of the limb deficient child in North Africa

Abstract: The surgical and prosthetic treatment of longitudinal lower limb deficiency is described and discussed, in the light of cultural and social requirements. Those with upper limb deficiencies are not fitted with prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
2
0
0
Order By: Relevance
“…Secondary operations have often been reported in other studies (Sliman et al, 1991;Aitken, 1963) and the same was found in the present study. Overgrowth of the bone has often been mentioned by others, with a prevalence of 4 to 35% (Davids et al, 1995).…”
Section: Secondary Complicationssupporting
confidence: 92%
See 1 more Smart Citation
“…Secondary operations have often been reported in other studies (Sliman et al, 1991;Aitken, 1963) and the same was found in the present study. Overgrowth of the bone has often been mentioned by others, with a prevalence of 4 to 35% (Davids et al, 1995).…”
Section: Secondary Complicationssupporting
confidence: 92%
“…In general the children's functional abilities were found to be satisfactory. The same has been found in other studies (Jones and Lipson, 1991;J0rring, 1971), even in third world countries (Sliman et al, 1991;Jain, 1994), although children in these countries experienced more difficulties in the fitting of prostheses (Fernandez-Palazzi et al, 1991). Jones and Lipson (1991) mentioned that in Australia children with a leg amputation were well integrated into the school and sporting life of ordinary childhood, although they gave no exact data.…”
Section: Functional Abilitiessupporting
confidence: 74%